2015
DOI: 10.1016/j.cmet.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Modulates Electrolyte Balance and Blood Pressure through Effects on Distal Cell Voltage and Chloride

Abstract: SUMMARY Dietary potassium deficiency, common in Western diets, raises blood pressure and enhances salt sensitivity. Potassium homeostasis requires a molecular switch in the distal convoluted tubule (DCT), which fails in familial hyperkalemic hypertension (pseudohypoaldosteronism type 2), activating the thiazide-sensitive NaCl cotransporter, NCC. Here, we show that dietary potassium deficiency activates NCC, even in the setting of high salt intake, thereby causing sodium retention and a rise in blood pressure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
560
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(595 citation statements)
references
References 43 publications
29
560
4
2
Order By: Relevance
“…For example, Na + restriction, diuretic treatment and MR inhibition activate the renin-angiotensin system, and angiotensin II is a known potent NCC regulator [13,33]. Likewise, aldosterone-as well as furosemide administration cause hypokalemia, which may activate NCC by direct effects on DCT plasma membrane voltage, intracellular chloride concentrations, and WNK/SPAK activity [29]. Interestingly, we also observed that the two days of dietary sodium restriction lowered plasma K + levels in mice.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…For example, Na + restriction, diuretic treatment and MR inhibition activate the renin-angiotensin system, and angiotensin II is a known potent NCC regulator [13,33]. Likewise, aldosterone-as well as furosemide administration cause hypokalemia, which may activate NCC by direct effects on DCT plasma membrane voltage, intracellular chloride concentrations, and WNK/SPAK activity [29]. Interestingly, we also observed that the two days of dietary sodium restriction lowered plasma K + levels in mice.…”
Section: Discussionmentioning
confidence: 50%
“…Nevertheless, it remains unclear whether the effects of aldosterone on NCC are mediated directly via the MR or might be secondary to changes provoked at the systemic levels. For example, hyperaldosteronism causes hypokalemia [20] which is known to profoundly affect NCC [25,29]. Moreover, it is important to note that the enzyme 11-ÎČ-hydroxysteroid-dehydrogenase type 2 (11ÎČHSD2), protecting the MR from activation by glucocorticoids through rapid metabolization of cortisol in humans and corticosterone in rodents, is significantly expressed only in the endportion of the DCT (DCT2) and the CS [2,5,10].…”
Section: Introductionmentioning
confidence: 99%
“…The localization of the mineralocorticoid receptor in the ASDN and other renal cell types 16 and/or a largely aldosteroneindependent ENaC function in the DCT2/ CNT 17 may contribute to the complexity of corticosteroid effects on ASDN function. A cross-talk between the angiotensin II membrane receptor and the mineralocorticoid receptor signaling pathways is well established, which was shown by Shibata et al 18 and Terker et al 19 Conditional inactivation of the mineralocorticoid receptor in the CD and late CNT is only compensated under standard diet but not when sodium supply is limited. 20 The phenotype is, thus, comparable with that of late CNT/CD-specific ENaC knockout, where the same AQP2-Cre transgenic line was used.…”
Section: Rescue Of Sodium and Potassiummentioning
confidence: 88%
“…Other stimuli for aldosterone secretion, such as hyperkalemia, may selectively upregulate KS-WNK1 protein expression via additional undefined mechanisms to attenuate L-WNK1 and NCC activity (55,59,60). Such effects may act in concert with changes in intracellular [Cl-] to suppress WNK activity (61). Additionally, other SGK1-dependent effects on NCC, including suppression of WNK4-mediated NCC degradation (46) or ubiquitylation of NCC by NEDD4-2 (35), are not shown here to highlight the mechanism of SPAK/OSR1 activation described in this study.…”
Section: Discussionmentioning
confidence: 99%